Polymorphism in the lymphotoxin-alpha gene, position +252 (rs909253), is not associated with preeclampsia development in Brazilian women - Cristina Wide Pissetti; Thiago Mantello Bianco; Sarah Cristina Sato Vaz Tanaka; Sueli Riul Da Silva; Marly Aparecida Spadotto Balarin (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSE: To investigate the frequencies of polymorphic allele and genotypes for the LT-α gene, position +252 (rs909253), in Brazilian women with preeclampsia.METHODS: This is a case-control study, in which 30 women with preeclampsia, classified according to the criteria of the National High Blood Pressure Education Program, and 115 women in the control group, with at least two healthy pregnancies, were selected. Peripheral blood was collected, and DNA was extracted, followed by genotyping, using specific primers and restriction analysis. The genotypes obtained were AA, AG and GG. Statistical analysis was performed using the χ2association test. The Hardy-Weinberg Equilibrium was tested using the Haploview Program.RESULTS: The results showed no association between genotypes and preeclampsia development (χ2=2.0; p=0.4). When the AG and GG genotypes were grouped according to allele G presence or absence (genotype AA), the data showed that the presence of allele G was not significantly different between cases (women with preeclampsia) and controls (χ2=0.0; p=1.0). The LT-α gene polymorphism, position +252 (rs909253), seems not to be an important candidate for the development of preeclampsia. Other inflammatory genes should be researched, and studies involving gene-environment interactions should be performed, in order to reach a better understanding of the etiology of the preeclampsia.